Duraplasty with Autologous Blood: A Cost-Effective and Efficient Alternative to Medical Products - HACIYAKUPOGLU, Ersin; Yüvrük, Evren; Yilmaz, Dervis Mansuri; Polat, Sait; Haciyakupoglu, Sebahattin (Journal of Neurological Surgery Part A: Central European Neurosurgery)
ABSTRACT Objective The aim of this experimental study was to investigate the effects of autologous plasma used as an alternative to duraplasty Materials and Methods We operated 21 patients and 8 New Zealand Rabbits and performed duraplasty with autologous blood. First heparin was added to autologous blood withdrawn from the patient/ rabbit, The sample was then centrifuged to obtain plasma. protamine sulfate was added to the plasma This mixture was then applied to the dural space and tumor cavity, resulting in fibrin formation within 2-3 minutes. All 21 patient had MRI scans 1 month after surgery to show neodura formation. 3 of our patients and all rabbit subjects were operated at least a month later and the biopsie was taken to show the neodura formation microsopically. Results In MRI scans, as well as in biopsies, we have detected the neodura formation. In rabbits that underwent experimental craniotomy and duratomy, neodura had formed as a weak, thin membrane that did not show continuity into the defect area after one month. In the control group, the distribution of collagen fibers appeared relatively normal in areas close to the intact dura. However, further from this area, the regular structure was disrupted, edematous areas had formed in the fibrous layers, and bone fragments were separated from the endosteal layer Conclusion The hypothesis of this study was that plasma obtained from the patient’s own arterial blood could serve as an alternative to traditional duraplasty materials. Plasma possesses many of the properties required for duraplasty material and can be a cost-effective, readily available option. Results demonstrate that autologous plasma does not induce significant histological changes and shows excellent biocompatibility with brain parenchyma. Therefore, autologous plasma can be considered a reliable and safe tissue sealant. It is easy to prepare and apply, remains stable in the operating room for 1-2 hours, and can be adjusted in size and thickness according to the dural defect and tumor cavity dimensions. SUMMARY Duraplasty is performed in the following cases: a.) When there are duramater tears of traumatic, spontaneous, or iatrogenic origin, or when associated with tumor invasion. b.) When primary suturing cannot be performed on the thinned duramater due to increased intracranial pressure, edema, contusion, or swelling. c.) When a drain is required for oozing bleeding of the parenchyma. d.) When compressive duratomy, craniotomy, or lobectomy has been performed. e.) In cases with pseudoencephalocele. f.) When constructive adaptation of the dura is required, such as in Chiari malformation. Since the 1800s, numerous allogeneic (homologous), xenogenic (heterologous), autologous, and biosynthetic graft materials have been used in duraplasty. However, none of these materials have proven to be superior to others. Therefore, the aim of this study was to use plasma obtained from the arterial blood of each subject as an alternative for duraplasty to fill dura defects and tumor cavities. Key words: Duraplasty, plasma, neodura, CSF leakageCraniectomy and duratomy were performed, followed by duraplasty using autologous arterial plasma. Brain and neodura biopsies were taken after one month. No significant complications developed. Magnetic resonance imaging was performed one month later to check for the formation of neodura. The results of light and electron microscopy examinations demonstrated that arterial plasma could be an alternative to traditional duraplasty methods.